Parametric study of ultra-intense laser interaction with uniform and nano-porous near-critical plasmas - S. Rezaei (AIP Advances, 2020)
Responses of the uniform near-critical plasma (UNCP) and nano-porous near-critical plasma (NPNCP) upon interaction with a short-intense laser have been scrutinized using two-dimensional (2D) particle-in-cell simulations. Maximum proton energy variation by the deposition of uniform and nano-porous layers in front of a solid target for a wide range of laser intensities (normalized amplitude a0 = 5–25) and average densities of the front layer ne = 0.3 − 3nc (where nc is the critical density) has been parametrically studied. It is found that the proton maximum energy for the front layers with sub-10 µm thicknesses is independent of the target porosity and density. However, in the relatively thick targets, the nano-porous structure decreases the laser energy absorption and, subsequently, the maximum proton energy compared to the uniform one. The results indicate that by employing UNCPs instead of NPNCPs, at the moderate laser intensity, the maximum proton energy reveals a 23% enhancement. This increment could be explained by rapid self-focusing of the laser pulse and dominant direct laser electron acceleration regime on the well-formed plasma channel in the UNCP layer. However, in the case of NPNCPs, the laser scattering from the plasma structure makes it less intense and more disordered, which influences the efficient laser energy coupling to the electrons.